Clinical application of the dried milk spot method for measuring tocilizumab concentrations in the breast milk of patients with rheumatoid arthritis. (10th April 2019) - Saito, Jumpei; Yakuwa, Naho; Kaneko, Kayoko; Nakajima, Ken; Takai, Chinatsu; Goto, Mikako; Yamatani, Akimasa; Murashima, Atsuko
Abstract: Aims: Tocilizumab (TCZ), a humanized anti‐interleukin‐6 receptor monoclonal antibody, is used to treat rheumatic diseases. There is limited information about the administration of TCZ during lactation. The dried spot method, a simple technique for processing biological samples which involves placement of a drop of specimen onto filter paper, has been used in clinical pharmacology to determine various drug concentrations. This study examined the feasibility of sample collection using the dried milk spot (DMS) method for obtaining data about the transfer of TCZ into breast milk. Methods: Concentrations of TCZ determined using DMSs prepared by patients were compared with those using liquid breast milk. Results: In an enzyme‐linked immunosorbent assay of TCZ in DMSs, the accuracy ranged from 93.0% to 113.8% and the precision ranged from 0.3% to 8.4%. All concentrations of TCZ were within 15% of the reference value when analyzed on separate days. TCZ in DMSs at room temperature, 4°C, and −20°C were stable for 28 days. Extracted TCZ concentrations from patient‐prepared DMSs were strongly correlated with those of liquid samples ( r  = 0.996). In a pharmacokinetic study, the median (range) maximum and minimum concentrations were 113 ng/mL (68‐205) and 8.5 ng/mL (4.8‐13.4), respectively. The milk‐to‐serum ratio at the trough TCZ concentration of 3 lactating mothers were 0.0015, 0.00082 and 0.0014. Conclusions: The DMS method for measuring TCZ transfer into breast milk may be reliable and feasible, and should contribute to evaluating the safety of breast‐fed infants whose mothers receive TCZ during lactation.